Adolescents’ Personality Development – A Question of Psychosocial Stress - Raufelder, Diana; Hoferichter, Frances; Kulakow, Stefan; Golde, Sabrina; Gleich, Tobias; Romund, Lydia; Lorenz, Robert C.; Pelz, Patricia; Beck, Anne (Frontiers in Psychology, 2021)
Following the relational-developmental systems approach, this three-wave study examines whether acute stress (T2) mediates the relationship between the development of personality traits from the beginning of 8th grade (T1, Mage = 15.63, SD = 0.59; 22 girls) to the end of 9th grade (T3). Using the Montréal Imaging Stress Task, which is a task that provokes acute social stress by negative social feedback, this study combined the functional magnetic resonance imaging (fMRI), heart rate, and longitudinal survey data of 41 adolescents. Mediation analysis revealed that stress-induced left insula activation partially mediates the longitudinal stability of conscientiousness. These results highlight the impact of negative social feedback during stress on students’ personality development.